2019
DOI: 10.1039/c9ra05889c
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between β-cyclodextrin and tea catechins, and potential anti-osteoclastogenesis activity of the (−)-epigallocatechin-3-gallate–β-cyclodextrin complex

Abstract: The EGCG–β-CD complex inhibited osteoclastogenesis significantly more than EGCG, and the molecular mechanism was closely associated with the downregulation of NFATc1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…aureus effectively and promote the proliferation of osteoblasts; thus, they could be used for minimally invasive treatment of bone infection. Similarly, Xu et al reported that the β-cyclodextrin complexed with EGCG could inhibit osteoclast genesis significantly more than that of EGCG.…”
Section: Application Of the Tea-based Delivery Systemmentioning
confidence: 95%
“…aureus effectively and promote the proliferation of osteoblasts; thus, they could be used for minimally invasive treatment of bone infection. Similarly, Xu et al reported that the β-cyclodextrin complexed with EGCG could inhibit osteoclast genesis significantly more than that of EGCG.…”
Section: Application Of the Tea-based Delivery Systemmentioning
confidence: 95%
“…Analysis of the catechin content was performed using an HPLC system (Agilent Technologies 1260-series, Agilent, San Jose, CA, USA) and a UV detection system, as previously described [23]. The HPLC system for catechin, GA, and caffeine measurements consisted of a YMC-Triart C18 column (5 µm, 250 × 46 mm) and a UV/Vis detector.…”
Section: Liquid Chromatography Analysis and Radical-scavenging Assaymentioning
confidence: 99%